2022
DOI: 10.3390/genes13122400
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Potential Markers of N(4)-Acetylcytidine through acRIP-seq in Triple-Negative Breast Cancer

Abstract: Understanding the causes of tumorigenesis and progression in triple-receptor negative breast cancer (TNBC) can help the design of novel and personalized therapies and prognostic assessments. Abnormal RNA modification is a recently discovered process in TNBC development. TNBC samples from The Cancer Genome Atlas database were categorized according to the expression level of NAT10, which drives acetylation of cytidine in RNA to N(4)-acetylcytidine (ac4C) and affects mRNA stability. A total of 703 differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We used the high-quality dataset constructed by Su et al to evaluate our model. The dataset was derived from the experimental data of Arango et al ( Arango et al, 2018 ), which identified 4,250 ac4C peaks using the acRIP-seq method ( Zhang X. et al, 2022 ). Su et al ( Su et al, 2023 ) extracted sequences of 100 nt up and down as positive samples to create a reliable dataset, starting from the cytosine near each ac4C peak.…”
Section: Methodsmentioning
confidence: 99%
“…We used the high-quality dataset constructed by Su et al to evaluate our model. The dataset was derived from the experimental data of Arango et al ( Arango et al, 2018 ), which identified 4,250 ac4C peaks using the acRIP-seq method ( Zhang X. et al, 2022 ). Su et al ( Su et al, 2023 ) extracted sequences of 100 nt up and down as positive samples to create a reliable dataset, starting from the cytosine near each ac4C peak.…”
Section: Methodsmentioning
confidence: 99%
“…NAT10, the sole protein encompassing both an N-acetyltransferase structural domain and a nucleotide-binding region, is regarded as an ac4C ‘writer’ protein responsible for governing RNA modification mechanisms. In cancer, NAT10 is usually expressed at high levels to maintain mRNA acetylation, which in turn promotes mRNA stability and translation 10 . Remodelin, as a novel small molecule, has been shown to reduce NAT10 activity 11 , thus preventing mRNA acetylation, and has been shown to be an effective treatment for various types of tumors 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 106 ] collected TNBC tissue samples and classified them according to NAT10 expression to understand the role of ac 4 C modification in TNBC progression and help design new personalized treatment plans and prognostic assessment. They found 703 lncRNAs differentially expressed between the high and low NAT10 expression groups, of which 20 lncRNAs were associated with disease prognosis.…”
Section: Introductionmentioning
confidence: 99%